Not gently down the stream: flow induces amyloid bonding in environmental and pathological fungal biofilms - Peter N. Lipke (mBio)
ABSTRACT Surface-bound biofilms are the predominant microbial life form in the environment and host organisms. Many biofilms survive and thrive under physical stress from liquid flow in streams, fuel lines, blood, and airways. Strategies for biofilm persistence include shear-dependent adhesion (called catch bonding). In some cases, biofilms are physically strengthened by the formation of cross-β bonds between proteins: the same process that generates amyloids. Cross-β bonds have low dissociation rates. In biofilms, they bind cells to substrates, each other, and the biofilm matrix. Most fungal adhesins include amino acid sequences that can form amyloids. Shear flow activates these adhesins by unfolding pseudo-stable protein domains. The unfolding exposes sequence segments that can form cross-β bonds. These segments interact to form high-avidity adhesin patches on the cell surface. Thus, cross-β bonding is a consequence of flow-induced exposure of the cross-β core sequences. Liquid flow leads to both biofilm establishment through catch bonding and biofilm strengthening through amyloid-like bonds. This shear-dependent induction of biofilm establishment and persistence is a model for many microbial systems.IMPORTANCEThe microbes in biofilms persist in many environments, including industrial and pathological settings. These surface-associated communities show high resistance to antibiotics and microbicides. Biofilms also resist scouring by liquid flow. Amyloid-like cross-β bonds allow the establishment, strengthening, and persistence of many biofilms. This discovery opens a window on the novel use of anti-amyloid strategies to control microbes in biofilms.